A Taylor Seeeerieeees

Calculus Level 2

Determine the Taylor series for the function f ( x ) = e x centered at x = 2. f(x) = e^x \text{ centered at } x = 2.

n = 0 e ( x 2 ) n n ! \sum_{n=0}^{\infty} \frac{e(x - 2)^n}{n!} n = 1 e 2 ( x 2 ) n n ! \sum_{n=1}^{\infty} \frac{e^2(x - 2)^n}{n!} n = 0 e 2 ( x 2 ) n n ! \sum_{n=0}^{\infty} \frac{e^2(x - 2)^n}{n!} n = 1 e ( x 2 ) n n ! \sum_{n=1}^{\infty} \frac{e(x - 2)^n}{n!}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Pranshu Gaba
Aug 31, 2015

The Taylor series of a function f ( x ) f(x) centered at x = x 0 x = x_{0} is n = 0 f ( n ) ( x 0 ) ( x x 0 ) n n ! \displaystyle\sum _{n = 0} ^{\infty} f^{(n)} (x_{0}) \frac{(x - x_{0}) ^{n}}{n!}

In this case our function f ( x ) f(x) is e x e^{x} and x 0 = 2 x_{0} = 2 . The n th n^{\text{th}} derivative of e x e^x is e x e^x itself, so f ( n ) ( 2 ) = e 2 f^{(n)} (2) = e^2 for all n n . Thus the Taylor series of f ( x ) = e x f(x) = e^x centered at x = 2 x = 2 is n = 0 e 2 ( x 2 ) n n ! \sum _{n = 0} ^{\infty} e^2 \frac{(x - 2) ^{n}}{n!} \ _\square

Moderator note:

Simple standard approach.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...